2018
DOI: 10.1177/1468017318762450
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of secondary traumatic stress among social workers: Supervision, income, and caseload size

Abstract: Summary In the past 20 years, research suggests that social workers and counselors are at risk of developing secondary traumatic stress from working with traumatized client populations. However, only a few studies have examined specific risk and protective factors that may buffer the social worker from developing secondary trauma symptoms. This article reports the results from a cross-sectional survey-based study of clinical social workers in which a predictive model of secondary traumatic stress was sought. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 49 publications
4
49
3
Order By: Relevance
“…Furthermore, when workers experience a high social pressure from their work, not perceiving the support of their colleagues increases the levels of secondary traumatic stress. Therefore, providing workers with resources, support, and recognition could increase their confidence in dealing with difficult situations within nursing homes settings (McCabe et al, 2017), and help reduce the levels of traumatic stress (Quinn et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, when workers experience a high social pressure from their work, not perceiving the support of their colleagues increases the levels of secondary traumatic stress. Therefore, providing workers with resources, support, and recognition could increase their confidence in dealing with difficult situations within nursing homes settings (McCabe et al, 2017), and help reduce the levels of traumatic stress (Quinn et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this population is at high risk for developing post-traumatic stress (Cai et al, 2020). More specifically, these professionals could be at risk of experiencing secondary traumatic stress-a set of psychological symptoms acquired from exposure to people who have experienced trauma (Quinn et al, 2019). These are reactions derived from the performance of a traumatic work task that can be exacerbated when mixed with high degrees of empathy, as is the case of workers in this sector during this health crisis (Ludick & Figley, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since increasing age [ 125 , 126 , 127 , 128 ] and work experience [ 129 , 130 ] are two of the most frequently reported protective factors against compassion fatigue, listening to an experienced professional might afford effective coping strategies to mental health professionals vulnerable to compassion fatigue. For instance, in a sample of 107 Licensed Master’s Social Workers (LMSWs), Quinn, Ji and Nackerud [ 131 ] demonstrated that LMSWs who positively appraised clinical supervision experienced fewer symptoms of secondary traumatic stress. In the two studies included in the present review which investigated the role of supervision [ 85 , 86 ], the relationship of frequency and quality of supervision were not examined simultaneously with compassion fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Some organisational factors that influence stress have been identified as low organisational support, limited resources and poor IT systems (Beer, 2016). Poor pay, elevated caseloads and the blame culture have been associated with retention issues in social workers (McGregor, 2014; Quinn et al, 2018). The interaction between high work demands, low levels of control and poor managerial support have been related to social worker stress (Ravalier, 2018), and the combination of high work pressures, lack of control over decision making and resources are detrimental to their job satisfaction (Wilberforce et al, 2014).…”
Section: Introductionmentioning
confidence: 99%